Attitudes of Saudi parents toward separation from their children during dental treatment - Manal Abushal; Joseph O. Adenubi (Elsevier, 2009)
Objective: The purpose of this study was to investigate the attitudes of Saudi parents to being separated or not separated from their children in the dental office and to assess the factors affecting such attitudes. Method: Five hundred and five parents participated in the study by completing a questionnaire which included questions related to their sex, marital status, job, family income and reasons for seeking dental treatment for the child. Questions were also designed to determine the responses and attitudes of the parents regarding their presence in the dental clinic. Results: Ninety-seven percent of the respondents preferred to stay with their children during dental treatment of their children. The main reason given by 83% of the parents was that the child would feel safe. More than 72% of the parents reported that they would reduce their child's fear and comfort him/her during the dental treatment. Conclusions: From the parent's point of view, the most threatening dental procedure undergone by their children was dental anesthesia (87.7%) followed by the use of dental drills (55.4%). It can be concluded from the results that majority of Saudi parents studied preferred to stay with their children during treatment. Dentists should consider this when treating children.